Functional SARS-CoV-2-specific T cells of donor origin in allogeneic stem cell transplant recipients of a T-cell-replete infusion: A prospective observational study - La Rosa, Corinna; Chiuppesi, Flavia; Park, Yoonsuh; Zhou, Qiao; Yang, Dongyun; Gendzekhadze, Ketevan; Ly, Minh; Li, Jing; Kaltcheva, Teodora; Ortega Francisco, Sandra; Gutierrez, Miguel-Angel; Ali, Haris; et al. (Frontiers in Immunology, 2023)
In the current post-pandemic era, recipients of an allogeneic hematopoietic stem cell transplant (HCT) deserve special attention. In these vulnerable patients, vaccine effectiveness is reduced by post-transplant immune-suppressive therapy; consequently, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease (COVID-19) is often associated with elevated morbidity and mortality. Characterizing SARS-CoV-2 adaptive immunity transfer from immune donors to HCT recipients in the context of immunosuppression will help identify optimal timing and vaccination strategies that can provide adequate protection to HCT recipients against infection with evolving SARS-CoV-2 variants. We performed a prospective observational study (NCT04666025 at ClinicalTrials.gov) to longitudinally monitor the transfer of SARS-CoV-2-specific antiviral immunity from HCT donors, who were either vaccinated or had a history of COVID-19, to their recipients via T-cell replete graft. Levels, function, and quality of SARS-CoV-2-specific immune responses were longitudinally analyzed up to 6 months post-HCT in 14 matched unrelated donor/recipients and four haploidentical donor/recipient pairs. A markedly skewed donor-derived SARS-CoV-2 CD4 T-cell response was measurable in 15 (83%) recipients. It showed a polarized Th1 functional profile, with the prevalence of central memory phenotype subsets. SARS-CoV-2-specific IFN-γ was detectable throughout the observation period, including early post-transplant (day +30). Functionally experienced SARS-CoV-2 Th1-type T cells promptly expanded in two recipients at the time of post-HCT vaccination and in two others who were infected and survived post-transplant COVID-19 infection. Our data suggest that donor-derived SARS-CoV-2 T-cell responses are functional in immunosuppressed recipients and may play a critical role in post-HCT vaccine response and protection from the fatal disease. Clinical trial registration clinicaltrials.gov, identifier NCT04666025.